Study on Temperature Effects and Energy Resolution of Large-size BGO-SiPM Detector - SONG Luyang1, SU Jun1, , ZHANG Liyong1, CHEN Junfeng2, LIU Fengcheng1, QIN Zhiwei1, SHENG Yaode1, JIANG Xinzhi1, CHEN Xin1, LIN Shen1, HUANG Yitong1, WANG Lin1, SHEN Yangping3, JIN Shilun4, LU Fei5 (Yuanzineng kexue jishu, 2025)
The large scintillator γ-ray detector array plays an important role in studies within fields such as nuclear physics and nuclear astrophysics. The design of gamma-ray detector arrays is often constrained by the use of photomultiplier tubes (PMTs), whose substantial bulkiness introduces numerous design constraints, thereby limiting improvements in key performance metrics such as detection efficiency, compactness, and granularity. In contrast, silicon photomultipliers (SiPMs), characterized by their smaller size, offer a promising alternative that could overcome these constraints. However, in comparison to PMTs, SiPMs exhibit greater sensitivity to temperature variations. This increased sensitivity, when combined with the temperature dependence of scintillator light yields, exacerbates the operational complexity of the detection system. This study aims to investigate the effect of temperature on a large-size bismuth germanate (BGO) scintillator coupled with a SiPM array (BGO-SiPM), determine the optimal operating parameters across a range of temperatures, and assess the feasibility of using SiPMs in BGO detector arrays. A rectangular BGO scintillator with dimensions of 6 cm×6 cm×12 cm was coupled with an 8×8 channel SiPM array. The performances of the BGO-SiPM detector were tested rigorously across temperatures ranging from −40 ℃ to 40 ℃. By adjusting the operating voltage, optimal energy resolution was attained within this temperature range. For comparative analysis, the same BGO scintillator was also coupled with a PMT (BGO-PMT), and subjected to identical temperature conditions. Experimental results show that at temperatures above 20 ℃, the energy resolution of the BGO-SiPM detector deteriorated more rapidly with increasing temperature when compared to the BGO-PMT detector. This decline is primarily due to the rapid increase in SiPM dark current, which consequently reduces the signal-to-noise ratio. Notably, as the temperature drops below 20 ℃, the performance of both the BGO-SiPM and BGO-PMT detectors becomes comparable. However, the BGO-SiPM detector shows a slightly better improvement in energy resolution as temperatures decrease. This improvement is primarily due to the reduction in SiPM dark current, which enhances signal-to-noise ratio. In addition, this work investigated the temperature sensitivity of the peak channel position of the BGO-SiPM detector near 20 ℃. In conclusion, this study demonstrates that while the BGO-SiPM detector is more sensitive to temperature variations regarding peak position, potentially affecting its performance under different conditions, it provides certain advantages over the BGO-PMT detector in terms of energy resolution at lower temperatures. These findings serve as a significant reference for future applications of SiPMs in BGO detector arrays.